Formulasi Makanan Enteral Berbasis Pangan Lokal (Kedelai dan Wortel) untuk Penyandang Diabetes Mellitus: Formulation of Enteral Food Based on Local Ingredients (Soy Flour and Carrot) for Individuals with Diabetes Mellitus - Ibnu Zaki; Untari Untari; Dika Betaditya; Sifa Auia Wicaksari (Jurnal Keperawatan Berbudaya Sehat, 2026)
Individuals with diabetes mellitus with experience complications and oral dysfunction often require enteral nutrition which favorable nutrition such as soy and carrot. This study aimed to evaluate the acceptability, viscosity, and flow rate of soybean- and carrot-based enteral formulas intended for individuals with diabetes mellitus. A descriptive experimental study was conducted using three formulations (F1, F2, and F3). Nutrient composition was analyzed using NutriSurvey 2007. Physical characteristics were evaluated by viscosity and flow rate. Acceptability was assessed through hedonic and hedonic quality tests involving 31 semi-trained panelists. Organoleptic data were analyzed using the Kruskal–Wallis and Mann–Whitney tests. All formulations have an energy density close to 1 kcal/mL, with higher protein and lower carbohydrate contents than a commercial formula. The viscosity ranged from 50.17 to 99.43 cP, and the flow rate 0.32 to 0.67 mL/s. No significant differences were observed among the formulations regarding color, aroma, or taste (p > 0.05). However, texture differed significantly among the formulations (p = 0.028). Soy flour and carrot-based enteral formula have the potential to be used as an alternative enteral nutrition for individuals with diabetes mellitus.